Modelo de gestão estratégica e participativa para institutos federais: uma aplicação no Instituto Federal de Goiás - Ferreira, Kepler Benchimol (2016)
This dissertation presents a model of strategic and participative management to higher education institutions, built from the theoretical framework of strategic management, stakeholder theory, legal framework and management models. For the application of the model, was chosen the Instituto Federal de Goiás - IFG, whose performance is through 14 units distributed by the state of Goiás. Specifically, it aimed to: identify and classify the stakeholders of IFG; analyze its Institutional Development Plan (IDP); performing an institutional diagnosis of the organization, from the proposed model; and refine the model of strategic and participatory management, with its application. The methodology of this research is outlined in four followings stages: 1) bibliographic and documentary research; 2) presentation of the essential elements of strategic management theory and stakeholder; 3) proposal of strategic and participatory management model; 4) application of the model, with case study and organizational diagnosis. As a result, it presents a proposal for a strategic management model and participatory for the institutions of higher education, improved from its application in the IFG. This model could be used by them to meet the accreditation requirements and re-accreditation of the Ministry of Education and for the preparation of IDPs, as well as a strategic and participative action, to consider the expectations of its stakeholders in managing the organization.